Detection of brucellosis in cattle and evaluation of risk factors associated with the disease in workers slaughterhouse (Research, Society and Development, 2021)
Brucellosis is anthropozoonosis caused by Brucella spp. Among the zoonotic species, B. abortus is the main species affecting cattle and can easily be transmitted to humans. The purpose of this study was to investigate, through epidemiological inquiry and serological analysis,  animal and human health as related to smooth strain Brucella spp. in a slaughterhouse located in the southern region of the state of Bahia. For this purpose, blood samples were collected from workers and animals at a slaughterhouse together with the State Inspection Service. Then, the Buffered Acidified Plate Antigen test was performed for animals and humans, the Slow Agglutination Test was performed for humans only; and the Complement Fixation Test and the 2-Mercaptoethanol Brucella Agglutination test (2ME) were performed for animals only. In addition, an epidemiological inquiry was applied to workers in order to assess risk factors for the disease. After data analysis, it was concluded that infection by smooth strains of Brucella spp. was detected in 14.0% of the cattle. Additionally, one worker out 41 tested reactive to the disease.